HAK RESTITUSI BAGI ASISTEN/PEMBANTU RUMAH TANGGA (ART/PRT) KORBAN PENGANIAYAAN OLEH MAJIKAN BERBASIS NILAI KEADILAN BERMARTABAT - Karo, Rizky Karo (Jurnal Aktual Justice, 2023)
Assistants/Domestic Helpers (ART/PRT) are needed by people in urban areas. A household member/worker helps an employer manage household finances, take care of children, provide meals for the employer, etc. Of course, wages for domestic workers vary from household to household. Domestic workers can be treated harshly by their employers, who are only punished. To formulate the first question raised, what are the arrangements for perpetrators of crimes against domestic workers before the promulgation of the Domestic Workers Protection Bill (RUU PPRT)? How are compensation claims fulfilled against household members/domestic workers who are victims of crimes committed? The research method is a prescriptive legal method and the authors use qualitative analysis of secondary data in the form of primary, secondary and tertiary legal sources. Investigations have shown that domestic workers/domestic workers can still be protected by his Decree No. 2 of 2015 of the Ministry of Labor of the Republic of Indonesia, although his PPRT law has not been published at the time of writing this academic paper. There is a nature. About the protection of domestic workers and the Domestic Violence Elimination Act. Second, reparation by the perpetrator/employer of the crime as compensation to the victim/household member or her family is a form of justice and restores the dignity of the victim. Victim rights are governed by applicable laws and regulations.